Urdu Translation and Validation of Short Muslim Practice and Belief Scale in Pakistan. (11th May 2016) - Ghayas, Saba; Batool, Syeda Shahida
Abstract: The present study was conducted to translate and validate the Short Muslim Practice and Belief Scale (SMPBS) (AlMarri, Oei, & Al-Adawi, 2009 ) to have a culturally equivalent and linguistically accurate Urdu version for use in Pakistan. Forward backward translation method was used for translation followed by tryout of the scale. Urdu translated version of the scale was completed by 500 participants of different age groups ( M = 36.5, SD = 10.1). Based on a confirmatory factor analysis (CFA), results confirmed that a two-factor model with the factors practice and belief provided an excellent fit to the data with chi square 55.96 ( df = 26, p > .05), CFI =.96, GFI = .97, and RMSEA = .04. Cronbach's alpha reliability coefficient was .78. Cross-language validation determined on a sample of 60 participants was satisfactory. Convergent validity of the scale was established by finding its significant positive correlation with religious practice and belief scale ( r = .64, p < .001) and significant negative correlation with depression ( r = –.18, p < .001) revealed its divergent validity.